Increasing Public Knowledge About Covid-19 Prevention through The Implementation of Health Protocol and Self Medication - Nita Parisa; Mgs. Irsan Saleh; M. T. Kamaluddin; Theodorus; Evi Lusiana; Nia Savitri Tamzil (Conferences of Medical Sciences Dies Natalis, 2020)
Covid-19 is a disease caused by the SARS Cov-2 virus and attacks the respiratory tract. This disease spreads very quickly through droplets. Until now, there is no definitive therapy for this disease. However, prevention that can be done to prevent this disease are implementing health protocols, social distancing, increasing endurance by consuming nutritious foods, exercising and regular rest, stress management, and self-medication.